International Law and Humanitarian Assistance
IX, 141 p.
Keywords: It is becoming increasingly apparent that there are major gaps in International Humanitarian Law and Public International Law in the area of humanitarian assistance. In response international organizations such as the UN and the EU are developing their own legal frameworks for humanitarian assistance and the body of customary law and so-called international disaster response law is growing steadily. This however shows that a coherent body of law is far from being a given. The legal reality of international law pertaining to emergency response is rather broadly spread over various international legal fields and related documents, covering situations of armed conflict and natural disasters. This book is one of the first attempts of linking different legal areas in the growing field of what could be called the international law of humanitarian assistance.